Virulence of Pectobacterium carotovorum subsp. brasiliense on potato compared with that of other Pectobacterium and Dickeya species under climatic conditions prevailing in the Netherlands. (28th September 2016) - van der Wolf, J. M.; de Haan, E. G.; Kastelein, P.; Krijger, M.; de Haas, B. H.; Velvis, H.; Mendes, O.; Kooman‐Gersmann, M.; van der Zouwen, P. S.
Abstract : In western Europe, Pectobacterium carotovorum subsp. brasiliense is emerging as a causal agent of blackleg disease. In field experiments in the Netherlands, the virulence of this pathogen was compared with strains of other Dickeya and Pectobacterium species. In 2013 and 2014, seed potato tubers were vacuum infiltrated with high densities of bacteria (10 6  CFU mL −1 ) and planted in clay soil. Inoculation with P. carotovorum subsp. brasiliense and P. atrosepticum resulted in high disease incidences (75–95%), inoculation with D. solani and P. wasabiae led to incidences between 5% and 25%, but no significant disease development was observed in treatments with P. carotovorum subsp. carotovorum, D. dianthicola or the water control. Co‐inoculations of seed potatoes with P. carotovorum subsp. brasiliense and D. solani gave a similar disease incidence to inoculation with only P. carotovorum subsp. brasiliense . However, co‐inoculation of P. carotovorum subsp. brasiliense with P. wasabiae resulted in a decrease in disease incidence compared to inoculation with only P. carotovorum subsp. brasiliense . In 2015, seed potatoes were inoculated with increasing densities of P. carotovorum subsp. brasiliense, D. solani or P. atrosepticum (10 3 –10 6  CFU mL −1 ). After vacuum infiltration, even a low inoculum density resulted in high disease incidence. However, immersion without vacuum caused disease only at high bacterial densities. Specific TaqMan assays were evaluated and developed for detection of P. carotovorum subsp. brasiliense, P. wasabiae and P. atrosepticum and confirmed the presence of these pathogens in progeny tubers of plants derived from vacuum‐infiltrated seed tubers.